2012
DOI: 10.1002/pmj.21293
|View full text |Cite
|
Sign up to set email alerts
|

Project Management Knowledge and Effects on Construction Project Outcomes: An Empirical Study

Abstract: This study examines the relationships among the PMBOK ® Guide, project performance, customer satisfaction, and project success by assessing the efficacy of management techniques, tools, and skills for implementing infrastructure and building construction. Experienced interviewees from private engineering firms and public agencies were asked to complete a questionnaire, and the responses were analyzed by means of a structural equation model. The analytical results indicate the appropriateness of prioritizing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(45 citation statements)
references
References 39 publications
3
42
0
Order By: Relevance
“…Likewise, empirical evidence of the extent of the influence established here on MHPs, the results also generally are in line with findings reported in previous research on traditional "one-off" projects (Liu, 2009;Xie, 2002;Chou and Yang, 2012). However, it is interesting to note that, on mass housing, construction and engineering elements adopted are crucial in co-ordination and management of the construction process (Zairul and Rahinah, 2011), here in this study the variable -"construction elements and components adopted in design units in contract packages under scheme" is perceived to not significantly contribute to communication ineffectiveness.…”
Section: Discussion Of Findingssupporting
confidence: 92%
See 1 more Smart Citation
“…Likewise, empirical evidence of the extent of the influence established here on MHPs, the results also generally are in line with findings reported in previous research on traditional "one-off" projects (Liu, 2009;Xie, 2002;Chou and Yang, 2012). However, it is interesting to note that, on mass housing, construction and engineering elements adopted are crucial in co-ordination and management of the construction process (Zairul and Rahinah, 2011), here in this study the variable -"construction elements and components adopted in design units in contract packages under scheme" is perceived to not significantly contribute to communication ineffectiveness.…”
Section: Discussion Of Findingssupporting
confidence: 92%
“…This often induces challenges in communicating exact scope and content of preliminaries to capture all the various units contained in the package. Chou and Yang (2012) indicated that contract packaging on construction projects generally influences communication methods, communication requirements and reporting systems among the project participants and thus should be well defined before the start of the project in order to increase communication success.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Recently, Chou and Yang (2012) use the structural equation modeling (SEM) technique to prioritize the practice of the PMBOK Guide in the capital project industry. Based on a sample of 127 project managers and stakeholders, they reveal the interrelationships between the PMBOK Guide and project performance.…”
Section: Research Backgroundmentioning
confidence: 99%
“…These studies have contributed to establishing project management practices that lead to better project performance and/or have proved a positive relationship between the use of project management practices and project performance. However, there is a deficiency in research dedicated to provide quantitative information in detail about the implementation of project management practices (Aubry and Hobbs, 2010;Besner and Hobbs, 2013;Chou and Yang, 2012;Mir and Pinington, 2014;Thomas and Mullay, 2007). This may be due to the difficulties involved in analyzing and modeling them because of complex constructs (CookeDavies and Arzymanow, 2003;Din et al, 2011;Mir and Pinnington, 2014).…”
Section: Introductionmentioning
confidence: 98%